Efektivitas Penggunaan Variasi Metode Pembelajaran Fiqih Dalam Meningkatkan Motivasi Belajar di Kelas VII MTs Proyek Kandepag Medan - Hafizah Andhara; Jamiluddin Marpaung; Hotni Sari Harahap (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
This study aims to determine the effectiveness of various teaching methods in Fiqh to enhance students’ learning motivation in grade VII at MTs Project Kandepag Medan. This research is a qualitative study with a descriptive approach. The methods used include observation, interviews, and documentation to gather data regarding the implementation of diverse teaching methods and their impact on students’ learning motivation. The results reveal that the application of various teaching methods such as discussion, demonstration, question-and-answer, and group work creates a more active, enjoyable, and interactive learning atmosphere. These methods have been proven to increase students’ interest, attention, and participation in Fiqh learning. Thus, varied teaching methods in Fiqh are effective in improving students’ learning motivation in grade VII at MTs Project Kandepag Medan.